The sense in humour : a personal exploration of humour in the teaching of adults : some questions and tentative answers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University - Watt, Iain J (Massey University, 2007)
This thesis is a personal exploration of the potential applications of humour in the teaching of adults. I have provided some questions and tentative answers about the use of humour in the facilitation of adult learning. Having recognised the value of humour in my own teaching practice, I have examined the ways in which humour, when applied appropriately, can promote creative thinking by enhancing the processes of knowing, perceiving and discovering. Adult learning has been said to be a means of gaining knowledge and skills, a way to satisfy learner needs and a process of critical self-reflection that may lead to transformation. Adult education can involve challenging periods of transformation and students may require assistance to overcome inhibitions, behaviours and beliefs about themselves their culture and learning. In this thesis I have sought to explore how humour, manifesting itself in verbal, written and visual formats, may be a valuable pedagogical tool to address such issues. One of the purposes of this thesis is to contribute to knowledge in teaching practice by demonstrating that the systematic and informed introduction of humour into individual teaching strategics may provide a more people-centred climate which addresses individual and group learning needs from the perspective of teacher and student.
Keywords: Adult Education; Teaching; Humor in education